Management of a delayed post‐pancreatoduodenectomy haemorrhage using endovascular techniques. Issue 10 (31st July 2015) - Asai, Kengo; Zaydfudim, Victor; Truty, Mark; Reid‐Lombardo, KMarie; Kendrick, Michael; Que, Florencia; Nagorney, David; Andrews, James; Farnell, Michael
Abstract: Background: A delayed post‐pancreatoduodenectomy haemorrhage is associated with a significant increase in peri‐operative mortality. Endovascular techniques are frequently used for a delayed haemorrhage. However, limited data exists on the short‐ and long‐term outcomes of this approach. A retrospective review over a 10‐year period at a quaternary‐referral pancreatic centre was performed. Methods: Between 2002–2012, 1430 pancreatoduodenectomies were performed, and 32 patients had a delayed haemorrhage (occurring >24 h post‐operatively) managed by endovascular techniques. The clinicopathological variables related to a haemorrhage were investigated. Results: A total of 42 endovascular procedures were performed at a median of 25 days, with the majority of delayed haemorrhages occurring after 7 days. There were four deaths (13%) with three occurring in patients with a grade C haemorrhage. Seven patients (22%) experienced rebleeding, and two patients developed hepatic abscesses. Conclusion: A delayed haemorrhage post‐pancreaticoduodenectomy can be managed by endovascular techniques with acceptable morbidity and mortality. Rebleeding and hepatic abscesses may occur and can be managed non‐operatively in most cases. The association of a delayed haemorrhage with a pancreatic fistula makes this a challenging clinical problem.